2015
DOI: 10.1007/s11934-015-0544-4
|View full text |Cite
|
Sign up to set email alerts
|

Placebo Medication and Sham Surgery Responses in Benign Prostatic Hyperplasia Treatments: Implications for Clinical Trials

Abstract: Placebo medications and sham surgeries have long been thought to be inert treatments. These groups served as a threshold to which an active treatment should be compared in a randomized trial to determine the true efficacy of the active treatment. However, surprising changes in subjective symptom scores and objective measures of voiding have been demonstrated in numerous placebo medication or sham surgery arms of trials. The exact mechanisms by which these inactive treatments augment patient outcomes are not cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…Analyses of randomized, controlled clinical trials for LUTS/BPH with drugs, endoscopic procedures, and surgeries have shown that placebo effects are to be considered in evaluating the outcomes of active treatments 21,22. However, as the improvements in IPSS and Q max in this study are comparable to those observed in the prospective, controlled pivotal convective RF thermal therapy trial, and similarly durable,13 the validity of the therapeutic responses are substantiated.…”
Section: Discussionmentioning
confidence: 58%
“…Analyses of randomized, controlled clinical trials for LUTS/BPH with drugs, endoscopic procedures, and surgeries have shown that placebo effects are to be considered in evaluating the outcomes of active treatments 21,22. However, as the improvements in IPSS and Q max in this study are comparable to those observed in the prospective, controlled pivotal convective RF thermal therapy trial, and similarly durable,13 the validity of the therapeutic responses are substantiated.…”
Section: Discussionmentioning
confidence: 58%
“…These include multiple pain conditions (Tuttle et al 2015, Vase et al 2002, such as osteoarthritis (Bannuru et al 2015, Moseley et al 2002, migraine (Kam-Hansen et al 2014, IBS (Kaptchuk et al 2010, Vase et al 2005, and labor pain (Liberman 1967). Substantial placebo responses are also observed in depression (Cuijpers et al 2012, Fournier et al 2010, anxiety (Bandelow et al 2015), Parkinson's disease (Goetz et al 2008), schizophrenia (Rutherford et al 2014), asthma (Wechsler et al 2011), urological conditions (Sorokin et al 2015), menopausal hot flashes (Freeman et al 2015), and other conditions.…”
Section: Which Disorders Respond Most To Placebo Treatments?mentioning
confidence: 99%
“…Although placebo treatments can affect physiological outcomes, such as hormone production or urinary flow rate (Meissner 2011, Meissner et al 2007, Sorokin et al 2015, Wager & Atlas 2015, they are largest for psychological outcomes (Figure 2a) (Hróbjartsson & Gøtzsche 2010). For example, one study found that a placebo treatment for asthma improved subjective symptom severity but did not improve forced expiratory volume, an objective measure of lung function (Wechsler et al 2011).…”
Section: Which Disorders Respond Most To Placebo Treatments?mentioning
confidence: 99%
“…25 Disclosures about placebo responses should be carefully formulated to be as illness and symptom specific as possible. For example, for treatments of conditions that are known to elicit placebo responses (eg, benign prostatic hyperplasia, 26 perimenopausal hot flushes 27 ), patients should be told that previous studies suggest that they may experience symptom improvement. If no placebo effects are expected-for example, in trials that add a second medication to standard of care for treating cancer tumours-participants might be told that placebos are unlikely to affect the tumour and are designed to help scientists to assess outcomes objectively.…”
Section: Improving Disclosurementioning
confidence: 99%